Technical efficiency of small scale rice production in Adamawa state, Nigeria - Abba, Mohammed Wakili (Universiti Malaysia Sarawak, (UNIMAS), 2013)
Efficiency is a very important factor for measuringproductivity. In an economy where resources are scarce and the opportunities to use new technologies are limited, inefficiency studies indicate the potential possibility to raise productivity by improving efficiency without developing new technologies or increasing the resource base. The objective of this study is to analyze the technical efficiencies of small scale rain-fed and irrigated rice production in Adamawa State, Nigeria. The specific objectives are i) to estimate and compare the technical efficiency of the rice farmers, ii) to estimate and compare the costs and returns of rice production and iii) to determine the factors that causes of technical inefficiencies in rice production in the study area. A multistage sampling technique was used to select 375 rice farmers across Adamawa State under rainfed and irrigated rice production with the aid of structured questionnaires and the data were for 2010/2011 cropping season. Data were analyzed using the descriptive statistics, t-test statistics, Maximum Likelihood Estimate (MLE) of stochastic frontier and inefficiency model and the use of gross margin analysis. The results of the study show that male farmers constituted majority of the respondents represented by 96% in rain-fed and 86% in irrigated production system.Most of rice farmers 80% in irrigated and 68% in rain-fed are married and had a mean age of 42.8 years for irrigated rice production and 45.7 years for the rain-fed respectively.Regarding the literacy level, about 63% of the respondents havesome form of formal education in both the systems. The respondents were mostly small scale cultivating about 1.16 hectares of land in the irrigated system and 2.1 hectares v in the rain-fed system. The findings also revealed that majority of the respondents use their personal savings to finance their agricultural activities.